Production and characterization of cell-penetrating recombinant botulinum neurotoxin type A - Xuan Wei; Jiage Hu; Liling Jiang; Lu Li; Jia Liu (STAR Protocols, 2023)
Summary: We recently reported that fusion of cell-penetrating peptides (CPPs) to botulinum neurotoxin type A (BoNTA) proteins could improve the efficiency of cellular uptake. Here, we describe steps to produce and evaluate CPP-BoNTA fusion proteins. We present procedures for the expression and purification of recombinant CPP-BoNTA using insect-cell-based baculovirus expression vector system and in vitro characterization of purified proteins. We also detail the analysis of cellular uptake in cell culture and examination of the in vivo performance in mice.For complete details on the use and execution of this protocol, please refer to Wei et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.